A Piece of Greenland? Making Marketable and Artisan Gemstones. Issue 1 (1st March 2020) - Brichet, Nathalia
Abstract: This article explores the emergence of a Greenlandic mineral resource landscape against the background of the current establishment of an industrial ruby mine in Greenland. Anthropological fieldwork combined with a close reading of scientific reports, articles, and geological assessments about Greenlandic gemstones show a recurrent feature, namely that Greenlandic minerals get scaled and valued in ambiguous ways. This ambiguity is telling of a type of Danish (post-)colonial activity, even if such geological mapping was and is motivated by a dream of welfare, development, and economic sustainability shared by Danish experts and Greenlandic politicians alike. An overall point is to argue that the very practice of describing mineral resources also configures their perceived value and posits a yardstick by which to measure their potential.